APPLICATION OF ARTIFICIAL INTELLIGENCE IN ECONOMIC SECTORS - Shoakhmedova Nozima Khairullayevna; Dilbar Yusupova Mirabidovna (Scholar Express Journal, 2023)
This paper examines the application of Artificial Intelligence (AI) in economic sectors, highlighting its transformative effects on data analysis, forecasting, and decision-making processes. Through a literature review, we discuss the current research landscape and methodologies employed in the field. We present findings that demonstrate AI's effectiveness in various economic sectors and discuss future implications and possible changes. The article concludes with recommendations for further research and an overview of AI's overarching impact on these sectors.
Keywords: Artificial intelligence; economic networks; machine learning